2018
DOI: 10.3389/fphys.2018.01603
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Optimized CO Rebreathing Method for Measuring Blood Volumes and Hemoglobin Mass in Heart Failure Patients

Abstract: Introduction: Determination of blood volume, red cell volume, and plasma volume contributes to the understanding of the pathophysiology in heart failure, especially concerning anemia and volume load. The optimized carbon monoxide (CO)-rebreathing method (oCORM) is used to determine these parameters and hemoglobin mass (Hbmass) in exercise physiology. The applicability of oCORM to determine the intravascular volumes and Hbmass in heart failure patients is currently undetermined because assumptions concerning CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 27 publications
3
23
0
Order By: Relevance
“…In our study population, the median levels of CO reached 7.8% (7.0–8.8%) with no adverse events. The CO rebreathing test has been used in heart failure patients with reduced ejection fraction (<30%) with no observed cardiac adverse effects . The CO rebreathing test as performed in this study requires the patient to hold a mouthpiece for 6 minutes, which for some patients may be difficult to complete.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study population, the median levels of CO reached 7.8% (7.0–8.8%) with no adverse events. The CO rebreathing test has been used in heart failure patients with reduced ejection fraction (<30%) with no observed cardiac adverse effects . The CO rebreathing test as performed in this study requires the patient to hold a mouthpiece for 6 minutes, which for some patients may be difficult to complete.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonging the time before measuring the post‐CO rebreathing blood sample for %HbCO could improve the accuracy of the CO rebreathing test but the improvement beyond 10 minutes is very modest . A study of heart failure patients has found that reduced CO mixing resulted in a systematic underestimation the Hb mass below 1% …”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that any changes in COHb circulatory mixing kinetics in CLD do not necessitate adjustment of standard sample timings (Schmidt & Prommer, 2005), perhaps in contrast to the situation in heart failure (left ventricular ejection fraction < 30%) patients (Ahlgrim et al, 2018) and polycythemia (Wachsmuth et al, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…As such, measurement of COHb% at 6 and 8 min (averaged to yield the “7 min” value) is commended (Schmidt & Prommer, 2005), and was used in our study. However, mixing is delayed in disease states such as cardiac failure (Ahlgrim et al, 2018) and polycythemia (Wachsmuth, Soria, Jimenez, & Schmidt, 2019). Admixture might be slowed down in CLD due to changes in regional (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation